Little Red Book of Phrasal Verbs Little Red Book Series - Brien, O' Terry; Terry O'Brien (New Delhi, India Rupa Publications India Pvt. Ltd., 2012)
Little Red Book of Phrasal Verbs is a concise and accessible guide that offers a systematic study of English phrasal verbs. It delves into combinations of simple verbs with particles, explaining their meanings and usages. This book is an invaluable resource for students, writers, and language enthusiasts aiming to enhance their understanding and command of English phrasal verbs.
A concise and accessible guide that offers a systematic study of English phrasal verbs. It delves into combinations of simple verbs with particles, explaining their meanings and usages. This book is an invaluable resource for students, writers, and language enthusiasts aiming to enhance their understanding and command of English phrasal verbs.
Keywords: Little Red Book of Phrasal Verbs - Terry O'Brien